Study on the Economic Burden of Neurodevelopmental Diseases on Patients With Genetic Diagnosis - Xie, Donghua; Duan, Ruoyu; Li, Chen; Xie, Zhiqun; Wang, Aihua; Xiong, Lili; Wei, Jianhui; Xi, Hui; Fang, Junqu; Yan, Huifang; Wang, Junyu; Zhang, Yu; et al. (Frontiers in Public Health, 2022)
Objective To study the burden of neurodevelopmental diseases (NDDs) via health economics analysis of Chinese patients with genetic diagnosis. Methods We recruited NDD patients (0-18 years old) with genetic diagnosis (GD) from September 1, 2020 to January 30, 2021. We gathered basic information on the details of each diagnosis, as well as the direct and indirect costs before and after receiving GD. We corrected the costs for time biases by calculating the costs per day for each patient. Results For the 540 patients with NDDs, the mean age was 4.08±3.47. The median household income was 0.6 (0.4, 1.0) 10,000 CNY monthly. The direct and indirect costs were 12.27 (7.36, 22.23) 10,000 CNY, and 16.79 (6.23, 32.10) 10,000 CNY per patient, respectively. Every patient received 1.20 (0.34, 3.60) 10,000 CNY medially (15.91%) from insurance. The daily total costs after receiving a GD were approximately 62.48% lower than those before GD was given (191.59 CNY vs. 71.45 CNY). The lab cost decrease (95.77%, P＜0.05) was the largest, followed by drugs (91.39%, P＜0.05), hospitalization (90.85%, P＜0.05), and consultation (57.41%, P＜0.05). The cost of rehabilitation kept slightly increasing but there were no significant differences (P＞0.05). The daily direct medical costs of each patient fell by 75.26% (P＜0.05) from 311.79 CNY to 77.14 CNY when the diagnostic age was younger than 1, and declined by 49.30% (P＜0.05) and 8.97% (P＞0.05) when the diagnostic age was 1-3 and older than 3, respectively. Conclusions Early genetic diagnosis is crucial for to reducing the burden of disease because of the amount of money spent was lower when they are diagnosed at a younger age. Patients with NDDs can incur a heavy economic burden, especially in rehabilitation costs and indirect costs , because the insurance coverage for patients is low, so it is urgent for governments to pay more attention to these issues.